Efektifitas Psikoedukasi terhadap Kemampuan Keluarga Merawat Anggota Keluarga Penderita Hiv-Aids di Wilayah Kota Semarang - Riwayati, Riwayati; Hidayati, Eni (Jurnal Keperawatan Jiwa, 2015)
Immunodeficiency Virus) causes AIDS by infecting and damaging part of the body's defense (lymphocytes) which are a type of white blood cell in the immune system works to fight off infections. AIDS (Acquired Immune Deficiency Syndrome) is a set of symptoms as a result of exposure to the body is difficult to fight any germs. HIV / AIDS can be transmitted through direct contact with blood or body fluids of virus-infected person. Scientists generally believe that HIV-AIDS come from Sub-Saharan Africa. Now AIDS has become a disease outbreak. HIV-AIDS estimated 38.6 million people around the world. In January 2006, UNAIDS in collaboration with the WHO estimates that HIV-AIDS has killed more than 25 million people since it was first recognized on June 5, 1981. Provision of antiretroviral actually can reduce the mortality and severity of infection with HIV-AIDS, access to treatment is not available in all countries. Social punishment for people living with HIV / AIDS, are generally more severe when compared with patients with other deadly diseases. Sometimes the social penalties were also imposed on health workers or volunteers, who are involved in caring for people living with HIV / AIDS (PLWHA). The purpose of this study was to determine the effect on the ability of family psychoeducation therapy care for family members with HIV-AIDS in the city of Semarang. Quasi-experimental research design, with pre-post test approach without control group. The study was conducted in May-July 2014 in the region of Semarang and centralized in the Public Health Polyclinics, using random sampling as many as 30 families with HIV-AIDS sufferers. Family psychoeducation is a method of family therapy developed by NAMI (National Alliance for the Mentally III) to provide support to the family. Family psychoeducation is done is done through 5 stages of the session. Statistical test results dependent t-test showed a significant increase in the ability of the family after a family psychoeducation intervention (pvalue 0,00 ; ά=0,05). It is expected that the implementation of family psychoeducation to families with HIV and AIDS can be performed in any health care which in turn can be achieved free of HIV-AIDS Indonesia.